High Plains Aquifer study revisited: a 20-year retrospective for western Kansas - Peterson, Jeffrey M.; Bernardo, Daniel J. (My University, 2013)
The most comprehensive water policy analysis conducted on the High Plains region to date was the High Plains Ogallala Regional Aquifer Study completed in 1982. Twenty years later, we had a unique opportunity to compare the projections from this study with the changes that actually occurred over the past two decades. Specific comparisons were made for the area of western Kansas overlying the High Plains Aquifer. These comparisons revealed some significant differences in the status of the aquifer and in the region's economic development, relative to the predictions of the study. Most notably, contrary to the study's predictions, irrigated area did not decline precipitously, but rather continued to increase during the period. Despite large increases in irrigated area and production of more water-intensive crops, such as corn and alfalfa, both per-unit area and total water use declined over the 20 years. Differences in observed and projected results can be attributed to a variety of factors, including large differences in crop prices, yield trends, energy prices, farm commodity programs, and irrigation technologies relative to those assumed in the study. Future research will need to better account for these factors to offer useful guidance in setting water management policies.
Keywords: Agricultural economy; Energy prices; Irrigation; Ogallala aquifer; Water policy